GOALS-JWST: The Warm Molecular Outflows of the Merging Starburst Galaxy NGC 3256 - Thomas Bohn; Hanae Inami; Aditya Togi; Lee Armus; Thomas S.-Y. Lai; Loreto Barcos-Munoz; Yiqing Song; S. T. Linden; Jason Surace; Marina Bianchin; Vivian U; Aaron S. Evans; et al. (The Astrophysical Journal, 2024)
We present James Webb Space Telescope (JWST) integral-field spectrograph observations of NGC 3256, a local infrared-luminous late-stage merging system with two nuclei roughly 1 kpc apart, both of which have evidence of cold molecular outflows. Using JWST/NIRSpec and Mid-Infrared Instrument data sets, we investigate this morphologically complex system on spatial scales of <100 pc, where we focus on the warm molecular H _2 gas surrounding the nuclei. We detect collimated outflowing warm H _2 gas originating from the southern nucleus, though we do not find significant outflowing H _2 gas surrounding the northern nucleus. We measure maximum intrinsic outflow velocities of ∼1000 km s ^−1 , which extend out to a distance of 0.7 kpc. Based on H _2 S(7)/S(1) ratios, we find a larger fraction of warmer gas near the southern nucleus, which decreases with increasing distance from the nucleus, signifying the southern nucleus as a primary source of H _2 heating. The gas mass of the warm H _2 outflow component is estimated to be M _warm _,out = (1.4 ± 0.2) × 10 ^6 M _⊙ , as much as 6% of the cold H _2 mass estimated using Atacama Large Millimeter/submillimeter Array CO data. The outflow timescale is about 7 × 10 ^5 yr, resulting in a mass outflow rate ${\dot{M}}_{warm,out}=2.0± 0.8\,M_{\odot }\,{yr}^{-1}$ and kinetic power P _warm,out ∼ 4 × 10 ^41 erg s ^−1 . Lastly, regions within our 3.″0 × 3.″0 NIRSpec data, where the outflowing gas reside show high [Fe ii ]/Pa β and H _2 /Br γ line ratios, indicate enhanced mechanical heating caused by the outflows. The fluxes and ratios of polycyclic aromatic hydrocarbons (PAHs) in these regions are not significantly different compared to those elsewhere in the disk, suggesting the outflows may not significantly alter the PAH ionization state or grain size.